Scientific and technological innovation related to real economic growth - Xiaoning Cheryl Long (China Political Economy (CPE), 2019)
Purpose Innovation is the fundamental driving force for the long-term sustainable development of an economy. After four decades of rapid economic growth, China is facing crises related to a demographic structure of "aging before getting rich," industrial overcapacity of low-end products and environmental and resources constraints. This paper aims to discuss these issues. Design/methodology/approach Based on logical analysis and recapitulation of previous empirical research, this study presents the conclusion. Findings Scientific and technological innovation, as strategic support to improve social productivity and overall national strength, must be placed at the center of the country's overall development. Originality/value The development model that preys upon cheap resources for extensive growth is unsustainable. Thus, the country needs an urgent strategic switch to drive its economic growth through research and development innovation and original technological advancement.
Keywords: 330; Business environment; Real economy